Cheese whey: a cost-effective alternative for hyaluronic acid production by Streptococcus zooepidemicus - Amado, Isabel R. (2016)
This study focuses on the optimization of cheese whey formulated media for the production of hyaluronic acid HA by Streptococcus zooepidemicus. Culture media containing whey (W; 2.1 g/L) or whey hydrolysate (WH; 2.4 g/L) gave the highest HA productions. Both W and WH produced high yields on protein consumed, suggesting cheese whey is a good nitrogen source for S. zooepidemicus production of HA. Polysaccharide concentrations of 4.0 g/L and 3.2 g/L were produced in W and WH in a further scale-up to 5 L bioreactors, confirming the suitability of the low-cost nitrogen source. Cheese whey culture media provided high molecular weight (> 3000 kDa) HA products. This study revealed replacing the commercial peptone by the low-cost alternative could reduce HA production costs by up to a 70%compared to synthetic media.